Assessing the efficacy of a community-based screening program for undiagnosed hypertension. - Salimova, Toxtajan; Mirzaeva, Dilfuza; Anarboev, Sanjar; Mirzajonov, Azimjon; Khusenov, Olim; Kholmatov, Davron; Mukhayyo, Kattaboyeva; Kamilya, Baybekova; Zulfiya, Karimova (Revista Latinoamericana de Hipertensión, 2026)
Undiagnosed hypertension is common in Central Asia, yet community-based screening programs have not been rigorously evaluated in post-Soviet settings like Uzbekistan. We conducted a cluster-controlled trial across twelve mahallas (neighborhoods) in three districts, urban, peri-urban, and rural, between March and June 2025. A total of 1,050 adults participated. In intervention clusters, trained community volunteers performed initial blood pressure measurements and referred individuals with elevated readings (≥140/90 mmHg) to local facilities for confirmatory testing within 14 days. Control clusters received usual care. The primary outcome was the proportion of previously undiagnosed individuals who obtained a confirmed diagnosis and documented treatment plan within three months. It is plausible that the intervention would improve detection, but we were not entirely sure how much the rural–urban divide would matter. And indeed, the results were a bit counterintuitive. Among those with initial elevated readings, 42.4% in intervention clusters achieved the primary outcome versus 26.8% in controls (adjusted OR 2.04, 95% CI: 1.32–3.15). The effect was most pronounced in the rural district (absolute difference 26.3 percentage points) and weakest in the urban setting (7.1 points). Then again, loss to follow-up between screening and confirmatory visits reached nearly 30%, mainly driven by older age and rural residence. Common wisdom in the field suggests that such attrition is a major implementation hurdle, but our findings also show that those who do return are likely to receive treatment. This means that community-based screening can work – provided that the linkage to follow-up care is strengthened, particularly in remote areas. One might argue that the modest absolute gains (approximately 1 additional confirmed case per 6–7 screened) are still meaningful given the low baseline detection rates in rural Uzbekistan.